"Naturalization" of Routine Assisted Reproductive Technologies by In Vitro Culture of Embryos with Microvibration: Sex Ratio, Body Length, and Weight of 2, 456 Live-Birth Deliveries after Transfer of 9, 624 Embryos In Vitro Cultured in Static System and with Microvibration. (20th December 2017) - Isachenko, Vladimir; Sterzik, Karl; Isachenko, Evgenia; Maettner, Robert; Todorov, Plamen; Rahimi, Gohar; Mallmann, Peter; Strehler, Erwin; Pereligin, Igor; Alabart, José Luis; Merzenich, Markus
Abstract : Aim was to determine whether there is any difference in the sex ratio, body length, and body weight of 2, 456 deliveries after transfer of 9, 624 embryos derived using in vitro culture under static and mechanical microvibration conditions. Pronuclear embryos from 4435 patients were cultured in vitro under two different conditions: without (n = 4821 ) and with mechanical agitation (n = 4803 ). Sex ratio, body length, and weight of 2, 456 live-birth deliveries after transfer of 9, 624 embryos were noted. The proportion of males at birth was significantly associated with mode of in vitro culture of embryos only among women aged 40 years and older. The rate "body length" was significantly associated with mode of in vitro culture of embryos only among women aged 29 and younger. In the same time, among twins, this ratio positively associated with in vitro culture of embryos under microvibration only among women aged 30–34 years as well as ≥40 years and negatively among women aged 35–39 years. It was concluded that birth weight of infants was positively associated with mode of in vitro culture of embryos under microvibration among women of all age groups. This trial registration number is ISRCTN13773904, registered 6 April 2016.